Liprin-α1 modulates cancer cell signaling by transmembrane protein CD82 in adhesive membrane domains linked to cytoskeleton - Pehkonen H; Lento M; von Nandelstadh P; Filippou A; Grénman R; Lehti K; Monni O (My University, 2025)
Background
PPFIA1 is located at the 11q13 region commonly amplified in cancer. The protein liprin-α1 encoded by PPF1A1 contributes to the adhesive and invasive structures of cytoskeletal elements and is located at the invadosomes in cancer cells. However, the precise mechanism of liprin-α1 function in cancer progression has remained elusive.
Methods
Invasion regulating activity of liprin-α1 was examined by analyzing the functions of squamous cell carcinoma of head and neck (HNSCC) cell lines in three-dimensional collagen I after RNAi mediated gene knockdown. Transcriptome profiling and Gene Set Enrichment Analysis from HNSCC and breast cancer cells were used to identify expression changes relevant to specific cellular localizations, biological processes and signaling pathways after PPFIA1knockdown. The significance of the results was assessed by relevant statistical methods (Wald and Benjamini-Hochberg). Localization of proteins associated to liprin-α1 was studied by immunofluorescence in 2D and 3D conditions. The association of PPFIA1 amplification to HNSCC patient survival was explored using The Cancer Genome Atlas data.
Results
In this study, we show that liprin-α1 regulates biological processes related to membrane microdomains in breast carcinoma, as well as protein trafficking, cell-cell and cell-substrate contacts in HNSCC cell lines cultured in three-dimensional matrix. Importantly, we show that in all these cancer cells liprin-α1 knockdown leads to the upregulation of transmembrane protein CD82, which is a suppressor of metastasis in several solid tumors.
Conclusions
Our results provide novel information regarding the function of liprin-α1 in biological processes essential in cancer progression. The results reveal liprin-α1 as a novel regulator of CD82, linking liprin-α1 to the cancer cell invasion and metastasis pathways.